PENGEMBANGAN PROGRAM PEMBELAJARAN COOPERATIVE UNTUK MENINGKATKAN KREATIVITAS SISWA PADA PELAJARAN BAHASA INDONESIA DI SMP - Purtama , Hendri; Dewi, Happy Indira (LEMBAGA KAJIAN PEMBANGUNAN PERTANIAN DAN LINGKUNGAN (LKPPL), 2025)
The learning model at SMP Negeri 3 Batuatas is inefficient in enhancing student creativity because it generally uses the lecture method, also known as conventional learning. In this model, the teacher's role dominates, acting as the sole source of information, while students act as recipients. This study aims to develop and test the Cooperative Problem Solving (CPS) learning model to enhance student creativity in Indonesian language lessons at SMP Negeri 3 Batuatas, Southeast Sulawesi. This study employed both qualitative and quantitative methods. Qualitative data were obtained from assessments by material and language experts and learning design experts, which included responses, input, suggestions, and criticism. Meanwhile, quantitative data were collected through validation instruments for the learning tools used by the experts. The assessment results from the material and language experts indicated that the developed learning material product had achieved a very adequate qualification with a percentage of 92%. The validation results from product design experts showed that the developed learning model had achieved a very adequate qualification with a percentage of 77%.